A new species of Thyreophagus (Acari: Acaridae) from Brazil, with notes on species associated with stored food and human habitats and a key to species of this genus - Barbosa, Marina Ferraz De Camargo; Oconnor, Barry M.; Moraes, Gilberto José De (Zootaxa, 2016)
A new species Thyreophagus cracentiseta n. sp. is described morphologically based on adult females, adult homeomorphic and heteromorphic males collected from chicken feed in Brazil. The Thyreophagus species associated with stored food and human habitats are reviewed, and a key to separate species of this genus is provided.